2012
DOI: 10.15376/biores.7.2.1850-1865
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Thermo-Mechanically Treated Wood From Pinus Caribaea Var. Hondurensis

Abstract: This study aimed at evaluating the effect of thermo-mechanical treatment on properties of Pinus caribaea var. hondurensis wood. Two pressure levels (25% and 50% of the compression strength perpendicular to grain) were evaluated. The treatment was applied in a laboratory hot press in one-step or two-step modes for 50 minutes. In the one-step treatment, the total pressure was applied after the temperature of the center of the wood reached 170°C. In the two-steps treatment, half of the pressure was applied after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
0
6
0
3
Order By: Relevance
“…For wood also from the cerrado, Santos et al (2012), found radial, tangential and volumetric contractions of 4.12, 6.34 and 10.46%, respectively, and anisotropic factor of 1.54. Trianoski et al (2013), when evaluating the dimensional stability of tropical pine species, reported values of 2.42, 5.74 and 8.95% respectively for the radial, tangential and volumetric directions and an anisotropic coefficient of 2.52.…”
Section: Variation Of the Contraction Of The Wood By Diametric Class And Position In The Logmentioning
confidence: 94%
“…For wood also from the cerrado, Santos et al (2012), found radial, tangential and volumetric contractions of 4.12, 6.34 and 10.46%, respectively, and anisotropic factor of 1.54. Trianoski et al (2013), when evaluating the dimensional stability of tropical pine species, reported values of 2.42, 5.74 and 8.95% respectively for the radial, tangential and volumetric directions and an anisotropic coefficient of 2.52.…”
Section: Variation Of the Contraction Of The Wood By Diametric Class And Position In The Logmentioning
confidence: 94%
“…Therefore, it is important to know these variables behavior to improve the interaction between wood, finishing, and gluing products, since a surface with high wettability offers high glue line shear resistance (Freeman & Wangaard, 1960). Studies on tropical wood or hardwood wettability are scarce, but Boehme & Hora (1996), Kishino & Nakano (2004), and Buyuksari et al (2011) can be cited, as well as the studies carried out in Brazil by Soares et al (2011), Oliveira et al (2010) and Santos et al (2012). In this context, the objective of the present work was to evaluate the roughness and wettability of 11 Amazonian hardwoods.…”
Section: Introductionmentioning
confidence: 95%
“…Esses tratamentos permitem que a madeira tratada seja usada em condições menos favoráveis e competir com madeiras tropicais de custo superior (ESTEVES et al, 2007). YILDIZ et al, 2006;BRITO et al, 2008;MBURU et al, 2008;GONZÁLEZ-PEÑA et al, 2009 ESTEVES et al, 2005;BRITO et al, 2006;ESTEVES et al, 2007;DEL MENEZZI et al, 2009;BATISTA e KLITZKE, 2010;MODES, 2010;SANTOS et al, 2012 Uma forma bastante usual de avaliar melhoras na estabilidade dimensional de madeiras tratadas termicamente é utilizando o cálculo da eficiência anti contração (ASEanti-shrinking efficiency) e eficiência anti inchamento (ASEanti-swelling efficiency).…”
Section: Revisão Bibliográfica 1 -Eucalyptus Benthamii (Maiden E Cambunclassified
“…Esses cálculos têm sido usados por muitos pesquisadores e demonstram a eficiência do aumento da estabilidade dimensional (CAO et al, 2011;ESTEVES et al, 2005;ESTEVES et. al, 2007;TUONG e LI, 2010 ESTEVES et al, 2005;ESTEVES et al, 2007;DEL MENEZZI et al, 2009;BATISTA e KLITZKE, 2010;SANTOS et al, 2012 Hill (2006).…”
Section: Revisão Bibliográfica 1 -Eucalyptus Benthamii (Maiden E Cambunclassified
See 1 more Smart Citation